Clinical safety and possible efficacy of tirofiban in combination with intravenous thrombolysis by recombinant tissue plasminogen activator for early treatment of capsular warning syndrome (CWS) - Liu, Yunzhu; Li, Shiyong; Hao, Dongdong; Zhang, Zhongping; Yi, Yongxin; Fang, Jiayang; Lin, Weizhi; Zhang, Min (Frontiers in Neuroscience, 2022)
The purpose of this study was to assess the efficacy and safety of the combination of tirofiban with intravenous thrombolysis (IVT) in treating patients with capsular warning syndrome (CWS) who failed to respond to the treatment of intravenous thrombolysis alone. Tirofiban was approved for the treatment of CWS patients with fluctuating symptoms or no substantial improvement after intravenous thrombolysis within 24 h in our hospital from October 2019 to June 2021. Patients were evaluated with the National Institutes of Health Stroke Scale (NIHSS) at admission, at 72 h post-thrombolysis, at 1-week, and at 3-months with the modified Rankin Scales (MRS) score. A total of 12 patients received tirofiban and eight patients received control treatment with a history of CWS in our cohort. Among the patients, 13 patients smoked more than one pack of cigarettes a day, 17 had hypertension, 17 had hypercholesterolemia, 7 had diabetes, 1 had the history of cerebral infarction, 2 had atrial fibrillation, 7 had mild big vascular stenosis, 13 had lesions of the perforating branch by imaging, and 19 had acute capsular infarction. In both the tirofiban and control groups, NIHSS scores were significantly reduced after intravenous thrombolysis or 1-week after onset compared with before intravenous thrombolysis (P < 0.001). Before and after intravenous thrombolysis, there were no differences between the tirofiban group and control group (P = 0.970, P = 0.384, respectively). The tirofiban group, however, showed remarkably lower scores in both 1-week NIHSS and 3-month MRS than the control (P = 0.012, P = 0.003, respectively). Our study revealed that tirofiban did not increase the risk of hemorrhage and had favorable clinical efficacy as a remedial treatment for CWS patients with poor prognosis for intravenous thrombolysis, therefore indicating great potential for broader use.